2016
DOI: 10.3892/ol.2016.4756
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of the effect of TGF-β1 on U87 human glioblastoma cells

Abstract: Abstract. Glioblastoma multiforme (GBM) is the most widespread and aggressive type of primary brain tumor. The prognosis following diagnosis with GBM is poor, with a median survival time of 14 months. Tumor cell invasion, metastasis and proliferation are the major causes of mortality in patients with GBM. In order to develop effective GBM treatment methods it is necessary to identify novel targets involved in these processes. Recently, there has been increasing interest in investigating the signaling pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 80 publications
2
22
0
1
Order By: Relevance
“…The expression of CD248 and Sca-1 was negatively regulated, and the expression of ITGA8 was positively regulated by transforming growth factor (TGF)-β, which plays a critical role in the progression of fibrosis of IPF [15][16][17][18], suggesting that expression of CD248 and ITGA8 may be potentially changed in the pro-fibrotic state. However, like normal human lungs, the CD248 high ITGA8 low human fibroblast-like cells were localized in collagen fiberrich connective tissue, and CD248 low ITGA8 high human fibroblast-like cells were localized in elastic fiber-rich connective tissue (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CD248 and Sca-1 was negatively regulated, and the expression of ITGA8 was positively regulated by transforming growth factor (TGF)-β, which plays a critical role in the progression of fibrosis of IPF [15][16][17][18], suggesting that expression of CD248 and ITGA8 may be potentially changed in the pro-fibrotic state. However, like normal human lungs, the CD248 high ITGA8 low human fibroblast-like cells were localized in collagen fiberrich connective tissue, and CD248 low ITGA8 high human fibroblast-like cells were localized in elastic fiber-rich connective tissue (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As has been mentioned, the elements of TGF-β-signaling are considered to be potential targets for anti-tumor therapy [11][12][13][14][15][16]33]. In parallel, new approaches with the use of NSCs/NPCs are being developed for treatment of gliomas of brain [1][2][3][4][5][6][7][8].…”
Section: Resultsmentioning
confidence: 99%
“…This cytokine has been demonstrated to trigger EMT in certain cases of breast cancer ( 13 ), renal carcinoma ( 14 ), intestinal tumors ( 15 17 ), pancreatic cancer ( 18 ) and glioblastoma ( 19 ). Previous research ( 20 ) demonstrated that stimulation of U87 MG cell lines with TGF-β1 significantly increases the production of proteins associated with invasion, proliferation, migration, DNA regeneration, stemness, and resistance to drugs and radiation. The resulting pool of glioblastoma cells has a molecular phenotype that is very similar to that of CSCs ( 21 ).…”
Section: Introductionmentioning
confidence: 97%
“…The resulting pool of glioblastoma cells has a molecular phenotype that is very similar to that of CSCs ( 21 ). It was reported that in human glioblastoma tumor cells, only two signaling pathways (the integrin and focal adhesion pathways) are available for regulatory effects on gene expression processes in the CSC nucleus ( 20 ).…”
Section: Introductionmentioning
confidence: 99%